INOVASI PUSTAKAWAN DALAM PENGEMBANGAN LAYANAN PERPUSTAKAAN RISET DI BADAN RISET DAN INOVASI NASIONAL - Suci Wulandari; Tupan Tupan (Perpustakaan Nasional RI, 2022)
Librarians who work in research institute libraries are required to serve researchers optimally. To improve librarian services, it is necessary to innovate service development. Based on these problems, a librarian innovation study was conducted in the development of research library services at the National Research and Innovation Agency. The study aims to determine the innovation of librarians in the development of research library services; Providing online journal services and socializing online journal databases. The method used in this study for writing this article is through the method of observation and literature study. The results of the study indicate that the librarian's innovation in service development in the library is by developing services through intrabrin in providing services. The innovations developed include bibliometric services, literature review services, data visualization services and national scientific repository assistance services. To improve research results, librarians also provide online journal services that are subscribed to and conduct socialization for all research centers at BRIN.